Потребное управление при синтезе средств обеспечения устойчивости и управляемости летательного аппарата - Ковтонюк, И. Б.; Анипко, О. Б. (НТУ "ХПИ", 2009)
The method of synthesis of devices which provide stability and controllability of aircraft is offered in this work at the level of conception, allowing from all of aggregate of alternative va riants to choose such, which provide implementation of the set terms of flight and required level of pilotage properties taking into account present limits on the ranges of rejection of aircraft control.
Keywords: летательный аппарат; авиация; устойчивость; управляемость; авиационная техника; безопасность полетов; пилотирование